Formalizing the Logic and Proofs of Book I of Euclid’s Elements: Some Examples - José Gil-Férez; M. Andrew Moshier; Alberto Naibo; Marco Panza; Jean-Michel Salanskis (Philosophia Scientiæ)
The aim of this article is to study Euclid’s plane geometry, relatively to Book I of the Elements, from a formal point of view. Instead of making appeal to some already existent logical framework, we introduce a new formal language, as well as a new system of rules, specifically tailored to give a faithful reconstruction of Euclid’s proof practice. Such a reconstruction shows that Euclid’s work can be understood as resting on a very peculiar inferential setting, involving much more mathematics than logic (understood as a general framework of reasoning): inference rules essentially deal with geometric objects and their relations, while no propositional connectives nor quantifiers are present.